Scenario based land use simulation for climate adaptability in coastal urban agglomerations of Guangdong Hong Kong and Macao Bay area - Jiayu Wang; Junnan Liu; Ting Wang; Mengyuan Jia (Scientific Reports)
Abstract In the context of global climate change, coastal urban agglomerations encounter numerous challenges, especially under the condition of rapid urbanization, which consistently threatens human life, property, and well-being. This paper presents the Ecological-Risk Constrained Land Expansion Modeling Framework to explore the land expansion patterns of the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) coastal urban agglomeration from a climate adaptation perspective. We utilized InVEST and GIS to quantify the ecosystem services and coastal vulnerability index (CVI) of urban agglomerations, delimiting the ecological resilience regions and risk resilience regions as constraints for land expansion simulation. Eventually, we simulated five scenarios of land expansion in the GBA in 2035 using the patch-generating land use simulation (PLUS) model. The results reveal that: (1) The low-resilience ecological spaces are radially distributed in a cross shape along the Pearl River, Hongliqi River and Xijiang River, with Guangzhou, Foshan and Dongguan overlapping more with the regions that undergo severe loss of ecosystem services and a high degree of landscape fragmentation. (2) The medium–high resilience risk space constitutes approximately 19.4%, and coastal areas such as Tolo Harbour in Pak Shek Kok, Hong Kong, and Ma On Shan New Town are exposed to potential marine disaster risks. (3) The hotspot areas of land expansion in the five scenarios indicate that the construction land of future urban agglomerations will expand towards the southeast. (4) From the perspective of balancing ecological benefits and economic benefits, the ecology and risk integrated coordination (ERIC) scenario provides a superior balance. These results emphasize the imperative of coordinating ecological protection and risk avoidance strategies in future urban expansion to achieve the safe, compact and sustainable development of coastal urban agglomerations.